Thermal conditions of a medium-scale tropical enclosed hatchery for giant freshwater prawn, Macrobrachium rosenbergii de man - Kamarudin, Ahmad Kamil (2012)
This research was undertaken to study the indoor thermal conditions of a medium-scaled enclosed tropical freshwater prawn hatchery and their relationships with the larval rearing water temperature using in situ measurements and IES Virtual Environment software simulations. A typical enclosed prawn hatchery in Ipoh, Perak, Malaysia was chosen for the study. The results showed that the indoor air and water temperatures remained above upper comfort (30.7 °C) for human and optimal (30 °C) limit for prawn larval growth, respectively, for almost all daytime and beyond the hatchery operational period. The high temperatures were unfavourable for the workers’ comfort and prawn larval growth and survival especially during hot days. Two follow-up studies were conducted to improve the thermal conditions of the hatchery using the simulation software. In the first experiment, the performances of several insulation materials were studied. The results showed that the installation of roof insulation gave a cooler indoor thermal environment and provided a suitable water temperature or improved water thermal condition for the prawn larviculture. Although all tested insulation materials performed equally, the results suggested the reflective aluminium foil was the best roof insulation for the hatchery. In the second experiment, the performances of roof design (the original and an alternative jack roof with or without reflective aluminium foil, RAF) in improving the thermal conditions of the hatchery were evaluated. The results showed that the jack roof provided a massive improvement on the indoor thermal environment of the prawn hatchery close to the upper human acceptable thermal limit (34 °C). The installation of RAF to the jack roof further reduced the indoor air temperatures to a totally acceptable level for the occupants during daytime. Therefore, the combination of jack roof and reflective aluminium foil was recommended to achieve acceptable indoor thermal conditions for the workers while successfully maintaining the optimal thermal requirements for larval growth and survival.